Hubungan Antara Respon Petani pada Kegiatan Pelatihan dengan Peningkatan Produksi dan Pendapatan Usahatani Cabai Paprika (Capsicum anumm var.grossum) - Edeng edeng; Apriadi Azis (University of Insan Cendekia Mandiri, 2021)
The problem in this study is that the demand for paprika chili continues to increase, along with population growth, nutritional fulfillment, supermarkets, restaurants and export markets. but production so that the level of paprika chili production is still low in Indonesia. The efforts that have been taken are by forming legal entity farmer groups such as the Golden Gate Agricultural Cooperative in Cibodas Village, Lembang District, West Bandung Regency. Koptan G.E Aside from being a provider of saprotan and marketing containers, it is also a vehicle for learning for farmers. Educating member farmers is the main focus of this cooperative work program. The education program held at the G.E Cooperative is in the form of training. To increase the production of paprika chili, the G.E Cooperative held a training on paprika chili farming. This study aims to determine the relationship between the response of farmers to the training activities of paprika chili farming on the increase and production at the Koperasi Gerbang Emas Cibodas Village, Lembang District, West Bandung Regency. To achieve this goal, the type of research used is the case study method that takes the sample by means of saturated samples. The number of respondents was 16 paprika chili farmers who were members of the Gerbang Emas Cooperative who participated in the training of paprika chili farming in 2016. The conclusions from the research are: The application of cultivation techniques to the training of paprika chili farming at the Gerbang Emas Cooperative includes a good category with a cumulative score of 380 (87.96% of expectations). Increased production and income of farmers from GE Koptan members after applying the technical training included in the good category with a cumulative reality score of 262 (77.97% of reality). From the calculation results obtained rscount for 0.64 while rstable for N = 16 and α = 5% or 0.05 for the two-party test get 0.49. This means rscount > rstable or 0.64> 0.49. This means that Ho is rejected, thus there is a significant relationship between the response of farmers to training in paprika chili farming on increasing production and income .